ANALISIS DETERMINAN KESEJAHTERAAN KARYAWAN PT. SURYA MADISTRINDO CABANG DENPASAR - Hatta Wage; I Nyoman Sutama; A Asmini (Pusat Riset dan Publikasi, 2023)
This research was conducted with the aim of examining the determinants of employee welfare at PT. Surya Madistrindo Denpasar Branch consisting of salary, benefits, facilities, and promotion. This type of research is causal associative research. The type of data used is quantitative data in the form of scores on the results of respondents' answers which are collected directly using a questionnaire. The respondents of this study were employees of PT. Surya Madistrindo Denpasar Branch, totaling 34, were selected to represent all employees, totaling 146 people. Data collection was carried out using a questionnaire prepared based on the indicators of the research variables. All data that has been collected will be processed using the Statistical Program for Social Science (SPSS) program to be studied using techniques which include multiple linear regression analysis, individual parameter hypothesis testing (t test), simultaneous parameter hypothesis testing (F test), and determinant coefficient test (R2). The results of this study indicate that salaries, benefits, facilities and promotions have a positive and significant effect on the welfare of employees of PT. Surya Madistrido Denpasar Branch, either partially or simultaneously. The ability of the variables of salary, benefits, facilities and promotion to variations in changes in the variable welfare of employees of PT. Surya Madistrido Denpasar Branch is 86.7%, while the remaining 13.3% is influenced by other variables outside this research model.